2007
DOI: 10.1097/01.aog.0000287065.59491.70
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Course, and Risk Factors for Antenatal Anxiety and Depression

Abstract: II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

46
420
12
37

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 598 publications
(515 citation statements)
references
References 21 publications
46
420
12
37
Order By: Relevance
“…International studies performed with the same screening scale (EPDS), cutoff point (≥10) and postpartum period, have found lower prevalence, ranging from 13% to 24.2%. (15,16) Although studies have shown the ≥10 cut-off point of the EPDS as the best to detect PPD in public health services, we found only two studies adopting this recommendation, both of which showed a prevalence (26.9%) lower than that found in this study. (17,18) The prevalence of depressive symptomatology found in national studies that adopted cutoff points of 11/12 in the EPDS reveals indices between 28% and 39.4%, which is a reality closer to that found among the puerperal women investigated in this study.…”
Section: Discussioncontrasting
confidence: 55%
“…International studies performed with the same screening scale (EPDS), cutoff point (≥10) and postpartum period, have found lower prevalence, ranging from 13% to 24.2%. (15,16) Although studies have shown the ≥10 cut-off point of the EPDS as the best to detect PPD in public health services, we found only two studies adopting this recommendation, both of which showed a prevalence (26.9%) lower than that found in this study. (17,18) The prevalence of depressive symptomatology found in national studies that adopted cutoff points of 11/12 in the EPDS reveals indices between 28% and 39.4%, which is a reality closer to that found among the puerperal women investigated in this study.…”
Section: Discussioncontrasting
confidence: 55%
“…daily hassles), and each type of stress has varying degrees of severity. Depression and anxiety are mood disorders, which are also relatively common during pregnancy [8]. They are considered stress-related disorders, with repeat or chronic stress a risk factor and similar disruption of the underlying physiologic stress response [9,10].…”
Section: Physiology Of Maternal Distress During Pregnancymentioning
confidence: 99%
“…1 Pregnancy in adolescents is considered a risk factor for symptoms of depression, considering that Vanessa Polina Pereira COSTA (a) Marcos Britto CORREA (b) Marília Leão GOETTEMS (b) Ricardo Tavares PINHEIRO (c) Flávio Fernando DEMARCO (b) pregnant adolescents present a higher prevalence of depressive symptoms than nonpregnant adolescents (16-44% vs 5-20%). 2 High levels of anxiety symptoms are also common during pregnancy 3 and in the first year postpartum. 4 Moreover, continuous exposure to maternal symptoms of depression/anxiety has long-term negative consequences for child development, regardless of the contextual risk.…”
Section: Introductionmentioning
confidence: 99%